Bank capital in the short and in the long run - Caterina Mendicino; Kalin Nikolov; Javier Suárez; Dominik Supera (European Central Bank (ECB), 2019)
How far should capital requirements be raised in order to ensure a strong and resilient banking system without imposing undue costs on the real economy? Capital requirement increases make banks safer and are beneficial in the long run but also entail transition costs because their imposition reduces credit supply and aggregate demand on impact. In the baseline scenario of a quantitative macro-banking model, 25% of the long-run welfare gains are lost due to transitional costs. The strength of monetary policy accommodation and the degree of bank riskiness are key determinants of the trade-off between the short-run costs and long-run benefits from changes in capital requirements.
Keywords: E3; E44; G01; G21; 330; Macroprudential Policy; Default Risk; Effective Lower Bound; Transitional Dynamics